The Implementation of Competency Development of Health Administrator Through Training at The Directorate General of Health Workforce, Ministry of Health Republic of Indonesia - Murwaniyah Murwaniyah; Firman Hadi Rivai; R.N. Afsdy Saksono (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the factors that influence the implementation of competency development of Health Administrator and to recommends a model for implementing of competency development of Health Administrator through training at The Directorate General Of Health Workforce, Ministry of Health. Methods used is a Case Study with Qualitative Approach. Data collection is carried out through interview and document review. Research results show there are factors affecting the implementation of competency development of Health Administrator through training at the Directorate General Health Workforce has not been running optimally. First, the technical competency standards for functional health positions that will be used as a reference for competency development have not been completed, Second, there is no technical training that meets the needs of the technical competency gap in health administrators. Third, health administrators who take online training find it difficult to concentrate because they are still busy doing office work. Based on the results of study, the author formulates and recommends a model for implementing of competency development of Health Administrator through training.